Protective role of colitis in inflammatory arthritis via propionate-producing Bacteroides in the gut - Shon, Hoh-Jeong; Kim, Yu-Mi; Kim, Kyeong Seog; Choi, Jin-Ouk; Cho, Sang-Hyun; An, Sujin; Park, Se-Hyeon; Cho, Yong-Joon; Park, Joo-Hong; Seo, Sang-Uk; Cho, Joo-Youn; Kim, Wan-Uk; et al. (Frontiers in Immunology, 2023)
Objectives: To investigate whether and how inflammatory disease in the intestine influences the development of arthritis, considering that organ-to-organ communication is associated with many physiological and pathological events. Methods: First, mice were given drinking water containing dextran sodium sulfate (DSS) and then subjected to inflammatory arthritis. We compared the phenotypic symptoms between the cohoused and separately-housed mice. Next, donor mice were divided into DSS-treated and untreated groups and then cohoused with recipient mice. Arthritis was then induced in the recipients. The fecal microbiome was analyzed by 16S rRNA amplicon sequencing. We obtained type strains of the candidate bacteria and generated propionate-deficient mutant bacteria. Short-chain fatty acids were measured in the bacterial culture supernatant, serum, feces, and cecum contents using gas chromatography-mass spectrometry. Mice fed with candidate and mutant bacteria were subjected to inflammatory arthritis. Results: Contrary to expectations, the mice treated with DSS exhibited fewer symptoms of inflammatory arthritis. Intriguingly, the gut microbiota contributes, at least in part, to the improvement of colitis-mediated arthritis. Among the altered microorganisms, Bacteroides vulgatus and its higher taxonomic ranks were enriched in the DSS-treated mice. B. vulgatus, B. caccae, and B. thetaiotaomicron exerted anti-arthritic effects. Propionate production deficiency further prevented the protective effect of B. thetaiotaomicron on arthritis. Conclusions: We suggest a novel relationship between the gut and joints and an important role of the gut microbiota as communicators. Moreover, the propionate-producing Bacteroides species examined in this study may be a potential candidate for developing effective treatments for inflammatory arthritis.